META-ANALISIS PENGARUH STRATEGI PQ4R DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Mohammad Heru Dwi Kurniawan; Endang Sri Mujiwati; Ita Kurnia (Prima Magistra: Jurnal Ilmiah Kependidikan, 2020)
This research aimed to analyze the effect of the PQ4R strategy on Indonesian Language material. The PQ4R strategy was a learning strategy used that make students remember what they read and what they  can help in  teaching and learning process in the class which was conducted by reading the books. The research used a meta-analysis method by using two national journal articles. The calculations on the two articles provided  different results. The results of the first analysis article had an effect size of (1.33) which means that it had the highest effect size. While , in  the second article it had the effect size of (0.84) which means the effect size is high. The PQ4R strategy affected in  learning outcomes and it can be used in Indonesian in  the high of the elementary school.